2002
DOI: 10.1034/j.1399-3054.2002.1150207.x
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress affects chloroplast lipid metabolism in rape (Brassica napus) leaves

Abstract: Rape (Brassica napus L. var. Bienvenue) is a 16:3 plant which contains predominantly prokaryotic species of monogalactosyldiacylglycerol i.e. sn-1 C18, sn-2 C16 (C18/C16 MGDG). Rape plants were exposed to a restricted water supply for 12 days. Under drought conditions, considerable changes in lipid metabolism were observed. Drought stress provoked a decline in leaf polar lipids, which is mainly due to a decrease in MGDG content. Determination of molecular species in phosphatidylcholine (PC) and MGDG indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 30 publications
4
32
0
1
Order By: Relevance
“…6 A proposed model of the relationship between glycolysis and MGDG synthesis (refer to Shen and Wang 1991;Kelly and Dormann 2002;Ichihara 2001). Gal Galactose, Gal-1-P galactose-1-phosphate, Glu-1-P glucosel-1-phosphate, UDP uridine diphosphate, TCA cycle tricarboxylic acid cycle, ACP acyl carrier protein, G-3-P glycerol-3-phosphate, LPA lysophosphatidic acid, PA phosphatidic acid, DG 1,2-diacyl-sn-glycerol, DGD2 an Arabidopsis gene encoding a UDP-galactose-dependent digalactosyldiacylglycerol synthase, 16:0 length of carbon chain: number of double bonds in rape (Brassica napus) was reduced (Benhassaine-Kesri et al 2002). These results seem to contradict our data that OsMGD mRNA is increased by drought and salt treatment.…”
Section: Discussionmentioning
confidence: 99%
“…6 A proposed model of the relationship between glycolysis and MGDG synthesis (refer to Shen and Wang 1991;Kelly and Dormann 2002;Ichihara 2001). Gal Galactose, Gal-1-P galactose-1-phosphate, Glu-1-P glucosel-1-phosphate, UDP uridine diphosphate, TCA cycle tricarboxylic acid cycle, ACP acyl carrier protein, G-3-P glycerol-3-phosphate, LPA lysophosphatidic acid, PA phosphatidic acid, DG 1,2-diacyl-sn-glycerol, DGD2 an Arabidopsis gene encoding a UDP-galactose-dependent digalactosyldiacylglycerol synthase, 16:0 length of carbon chain: number of double bonds in rape (Brassica napus) was reduced (Benhassaine-Kesri et al 2002). These results seem to contradict our data that OsMGD mRNA is increased by drought and salt treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This experiment showed that rewatering increased PSII capacity. Severe soil drought resulted in cell-membrane damage (Benhassaine-Kesri et al, 2002), and a decrease in leaf photosynthetic capacity (García and Lamattina, 2001;Xu and Zhou, 2006b). However, rewatering after long-term drought may repair the damage and stimulate the well photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This membrane restructuring is thought to arise from the necessity of maintaining membrane order or fluidity (Benhassaine-Kesri et al 2002). Changes in the contents of leaf lipids that are induced by water deficiency depend on the plant's sensitivity or tolerance to drought.…”
Section: Introductionmentioning
confidence: 99%